Epidemiological Studies on Haemoparasitic Infections of Horses in North Central Nigeria - Shola David Ola-Fadunsin; Chukwuemeka Peter Orie; Isau Aremu Ganiyu; Oluyomi Olajumoke Ogunleye; Adakole Sylvanus Adah; Olufunmilayo Josephine Ola-Fadunsin; Deborah Arimie Adah; Oluwafemi Babatunde Daodu (Universitas Airlangga, 2026)
Background: Haemoparasite infections represent a major cause of equine morbidity and mortality. This study was conducted to determine the prevalence, species distribution, and risk factors of these infections among horses in Kwara and Niger States, North Central Nigeria. Purpose: Investigating the occurrence of both single and mixed haemoparasite species, this research examined how factors such as age, body condition, and packed cell volume (PCV) influence infection rates in apparently healthy horses. Method: Sampling was performed on 102 apparently healthy horses, followed by blood collection and analysis via wet mount and thin blood smear techniques. Evaluation of the PCV was achieved using the haematocrit technique. For statistical analysis, univariate logistic regression was employed, with a value of p<0.05 considered statistically significant. Results: Positivity for at least one haemoparasite species was identified in 57 horses, representing 55.88% (95% CI: 46.21–65.13) of the sampled population. Detected were five distinct species: Anaplasma phagocytophilum, Babesia caballi, Theileria equi, Microfilaria of Setaria equina, and Trypanosoma equi identified as the most abundant at 34.31% (95% CI: 25.82–43.95). Furthermore, significant predictors associated with infection prevalence were determined to be age, body condition score, sex, PCV count, and horse ownership. Conclusion: Raised by the high infection rate in the study area is a noticeable concern regarding equine health. Underscored by these findings is the necessity for stringent control of ticks and other arthropod vectors to curtail the transmission of haemoparasites among horses within the region and across Nigeria.